PRELIMINARY STUDY ON THE HETEROTIC PATTERN OF TROPICAL QUALITY PROTEIN MAIZE (QPM) AND DOWNY MILDEW RESISTANCE (DMR) MAIZE INBREDS - D. Ruswandi (Zuriat, 2005)
Exploration of heterotic patterns among maize inbreds has become important since it could provide information on which new germplasm could be used to improve base population in breeding program. This experiment was a preliminary study on the heterotic relationships between tropical quality protein maize (QPM) and downy mildew resistance (DMR) maize inbreds based on analysis on combining ability. Seven tropical maize inbreds were crossed in a line × tester. One commercial hybrid from Bisi Company, Bisi 2, was included for the evaluation of hybrids as check cultivar. The result revealed that two heterotic groups has been recognized, i.e., major group consisted of CML 161, CML 163, CML 172, Nei 9008, and P345. Whereas the small group contains MR 10 and Ki 3. The hybrids and their parental inbreds were evaluated in Jatinangor, Indonesia (753 m above sea level) in 2003 to 2004. The location of yield test has a humid climate with an annual rainfall of about 1925 mm. The field experiment was arranged in a randomize block design with two replications. The present study revealed two heterotic groups: major group involving CML 161, CML 163, CML 172, Nei 9008, and Ki 3; and small group containing MR 10 and P 345. Moreover, the major group can be divided into two subgroups involving all CML lines for the first subgroup and Nei 9008 and Ki 3 for the second subgroup.